Mathematical reliability model of building components by Rayleigh = Matematyczny model oparty na rozkładzie Rayleigha zmian niezawodności elementów składowych budynku - Nowogońska, Beata (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The patterns of process situations play an important role in the monitoring of diagnostic processes. The adaptation of mathematical models describing the degradation processes in mechanical and electronic devices creates opportunities to develop diagnostic standards for buildings erected in traditional technology. This article presents a proposal for the prediction of building operational reliability, which is a prognostic process model within the full period of its use.
Keywords: niezawodność eksploatacyjna; stopień zużycia; rozkład Rayleigha; reliability prediction; degree of wear; Rayleigh distribution